Virtual ethnography of electronic word of mouth as a marketing enhancement - Rochmana, Sunnah Dwi; Winarti, Oktifani; Kusuma, Ade; Nurhaqiqi, Hanna; Achmad, Zainal Abidin; Bergerat, Valentin Ceretto (ETNOSIA : Jurnal Etnografi Indonesia, 2022)
Electronic Word of Mouth (e-WoM) is a form of promotion in the digital era by distributing and sharing visual content about a brand or product informally without commercial influence. This study aims to understand the enhancement of e-WoM as a promotional medium by the coffee blogger account @cafehitssurabaya. This study uses a qualitative research method with a virtual ethnographic approach. Researchers are participative and involved in e-WoM activities on @cafehitssurabaya. Data collection using virtual searches and online interviews via WhatsApp with eight informants, namely the owner of the @cafehitssurabaya account and seven active followers. The study results show that e-WoM helps disseminate visual content related to opinions, reviews, and recommendations for various coffee shops by @cafehitssurabaya so that it impacts promotions and encourages buying decisions for potential consumers. Furthermore, @cafehitssurabaya enhances e-WoM by interacting and discussing with followers as opinion seekers. This study concludes that the e-WoM process has become an effective promotional medium, forming a new culture of Instagram users to share their love for the tradition of drinking coffee and various coffees and delivering criticism and praise to different coffee shops.